An experimental investigation of the influence of deviant peers on own deviancy: a replication study - Mercer, N. (Journal of experimental criminology, 2018)
This study is a replication of a study examining the causal impact of a brief exposure to deviant peers on own deviant behavior, i.e., Paternoster et al. (Journal of Research in Crime and Delinquency, 50:476-503, 2013). This study retested this design using different monetary incentives and a female deviant peer.